Making pictorial print : media literacy and mass culture in British magazines, 1885-1918 - Hedley, Alison (Toronto ; Buffalo ; London : University of Toronto Press, 2021)
"At the end of the nineteenth century, print media dominated British popular culture, produced in greater variety and on a larger scale than ever before. Within decades, new visual and auditory media had ushered in a mechanized milieu, displacing print from its position at the heart of cultural life. During this period of intense change, illustrated magazines maintained a central position in the media landscape by transforming their letterpress orientation into a visual and multimodal one. Ultimately, this transformation was important for the new media cultures of the twentieth and twenty-first centuries. Making Pictorial Print recovers this chapter in the history of new media, applying concepts from media theory and the digital humanities to analyse four popular late-Victorian magazines - the Illustrated London News, the Graphic, Pearson's Magazine, and the Strand - and the scrapbook media that appropriated them. Using the concept of media literacy, these case studies demonstrate the ways in which periodical design aesthetics affected the terms of engagement presented to readers, creating opportunities for them to participate in and even contribute to popular culture. Shaped by publishers, advertisers, and readers themselves, the pages of these periodicals document the emergence of modern mass culture as we know it and offer insight into the new media of our digital present."--
Frontmatter -- Contents -- Illustrations -- Acknowledgments -- Introduction: A History of Victorian Print Media Literacy and the Technological Imagination -- 1. The Illustrated London News, Popular Illustrated Journalism, and the New Media Landscape, 1885-1907 -- 2. Imagining Consumer Culture: Reading Advertisements in the Illustrated London News and the Graphic, 1885-1906 -- 3. Imagining Subjectivity: Reading Data Visualizations in Pearson's Magazine, 1896-1902 -- 4. Imagining Print Production: Making Scrapbook Media, c. 1830-1918 -- 5. Imagining New Media Platforms: Taking Snapshots for the Strand, 1896-1918 -- Conclusion: Victorian Media Literacies and the Genealogy of the Present -- Notes -- Index -- STUDIES IN BOOK AND PRINT CULTURE
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on October 20, 2021).
JSTOR
Keywords: Illustrated periodicals -- Great Britain -- History -- 19th century; Illustrated periodicals -- Great Britain -- History -- 20th century; Mass media -- Great Britain -- History -- 19th century; Mass media -- Great Britain -- History -- 20th century; Popular culture -- Great Britain -- History -- 19th century; Popular culture -- Great Britain -- History -- 20th century; Magazines (Publications) -- Grande-Bretagne -- Histoire -- 19e siècle.; Magazines (Publications) -- Grande-Bretagne -- Histoire -- 20e siècle.; Médias -- Grande-Bretagne -- Histoire -- 19e siècle.; Médias -- Grande-Bretagne -- Histoire -- 20e siècle.; LITERARY CRITICISM / Modern / 19th Century .; Illustrated periodicals; Mass media; Popular culture; Great Britain; 1800-1999; Victorian periodicals; Victorian popular culture; history of advertisements; history of data; history of journalism; history of photography; illustration studies; magazine; nineteenth-century print culture; History